The Impact of E-Procurement Implementation, Procurement Officer Competency, And Internal Supervision on Execution of Goods and Services Procurement: a Case Study of the Provincial Government of North Sumatra - Winda Ocviana; Rahima Br Purba; Heriyati Chrisna (Sean Institute, 2025)
This study aims to analyze the effect of E-Procurement Implementation, Procurement Officer Competence, and Internal Supervision on the Implementation of Procurement of Goods and Services in the North Sumatra Provincial Government. Using a quantitative approach with regression analysis, the study found that E-Procurement has a positive and statistically significant effect on increasing the effectiveness of procurement implementation, in line with the principles of good governance. Procurement Officer Competence shows a positive direction of influence on procurement implementation, although it is not statistically significant in this model. Interestingly, Internal Supervision shows a significant negative correlation with the effectiveness of procurement implementation, indicating that excessive supervision intensity has the potential to hinder the efficiency and effectiveness of the procurement process. This finding contradicts conventional expectations and suggests the need for a critical evaluation of the implementation of the supervision mechanism. The implications of this study highlight the importance of optimizing the E-Procurement system and reviewing the effectiveness of the internal supervision mechanism in the context of implementing procurement of goods and services in the North Sumatra Provincial Government.